Effect of the pig rearing system on the final volatile profile of Iberian dry-cured ham as detected by PTR-ToF-MS - Sánchez del Pulgar, J; Soukoulis, C; Carrapiso, A I; Cappellin, L; Granitto, P; Aprea, E; Romano, A; Gasperi, F; Biasioli, F (Meat Science, 2013)
The volatile compound proﬁle of dry-cured Iberian ham lean and subcutaneous fat from pigs fattened outdoors on acorn and pasture (Montanera) or on high-oleic concentrated feed (Campo) was investigated by proton transfer reaction time-of-ﬂight mass spectrometry. In addition to the usual proton transfer ionization the novel switchable reagent ions system was implemented which allows the use of different precursor ions (H3O+ , NO+ and O2 + ). The analysis of the lean and subcutaneous fat volatile compounds allowed a good sample discrimination according to the diet. Differences were evident for several classes of compounds: in particular, Montanera hams showed higher concentrations of aldehydes and ketones and lower concentrations of sulfur-containing compounds compared to Campo hams. The use of NO+ as precursor ion conﬁrmed the results obtained with H3O+ in terms of classiﬁcation capability and provides additional analytical insights.
Keywords: aldehydes; Aldehydes: analysis; Animal Feed; Animal Husbandry; Animal Husbandry: methods; Animals; diet; Dietary Fats; Dietary Fats: analysis; Dietary Fats: pharmacology; Dry cured ham; Ions; Ketones; Ketones: analysis; Mass spectrometry; Mass Spectrometry: methods; meat; Meat: analysis; Nuts; Oleic Acid; Oleic Acid: pharmacology; Poaceae; Proton transfer reaction mass spectrometry; Quercus; Rearing system; subcutaneous fat; Subcutaneous Fat: metabolism; Sulfur Compounds; Sulfur Compounds: analysis; Swine; Switchable reagent ions; Time of flight; Volatile Organic Compounds; Volatile Organic Compounds: analysis

A possible approach for gel-based proteomic studies in recalcitrant woody plants. - Sebastiana, Mónica; Figueiredo, Andreia; Monteiro, Filipa; Martins, Joana; Franco, Catarina; Coelho, Ana Varela; Vaz, Fátima; Simões, Tânia; Penque, Deborah; Pais, Maria Salomé; Ferreira, Sílvia (SpringerPlus, 2013)
Woody plants are particularly difficult to investigate due to high phenolic, resin, and tannin contents and laborious sample preparation. In particular, protein isolation from woody plants for two-dimensional gel electrophoresis (2-DE) is challenging as secondary metabolites negatively interfere with protein extraction and separation. In this study, three protein extraction protocols, using TCA, phenol and ethanol as precipitation or extraction agents, were tested in order to select the more efficient for woody recalcitrant plant gel-based proteomics. Grapevine leaves, pine needles and cork oak ectomycorrhizal roots were used to represent woody plant species and tissues. The phenol protocol produced higher quality 2-DE gels, with increased number of resolved spots, better spot focusing and representation of all molecular mass and isoelectric point ranges tested. In order to test the compatibility of the phenol extracted proteomes with protein identification several spots were excised from the phenol gels and analyzed by mass spectrometry (MALDI-TOF/TOF). Regardless the incomplete genome/protein databases for the plant species under analysis, 49 proteins were identified by Peptide Mass Fingerprint (PMF). Proteomic data have been deposited to the ProteomeXchange with identifier PXD000224. Our results demonstrate the complexity of protein extraction from woody plant tissues and the suitability of the phenol protocol for obtaining high quality protein extracts for efficient 2-DE separation and downstream applications such as protein identification by mass spectrometry.
Keywords: 2-de; ectomycorrhizal roots; grapevine; Mass spectrometry; oak; pine; protein extraction

Rapid characterization of dry cured ham produced following different PDOs by proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS). - Del Pulgar, José Sánchez; Soukoulis, Christos; Biasioli, Franco; Cappellin, Luca; García, Carmen; Gasperi, Flavia; Granitto, Pablo; Märk, Tilmann D.; Piasentier, Edi; Schuhfried, Erna (Talanta, 2011)
In the present study, the recently developed proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS) technique was used for the rapid characterization of dry cured hams produced according to 4 of the most important Protected Designations of Origin (PDOs): an Iberian one (Dehesa de Extremadura) and three Italian ones (Prosciutto di San Daniele, Prosciutto di Parma and Prosciutto Toscano). In total, the headspace composition and respective concentration for nine Spanish and 37 Italian dry cured ham samples were analyzed by direct injection without any pre-treatment or pre-concentration. Firstly, we show that the rapid PTR-ToF-MS fingerprinting in conjunction with chemometrics (Principal Components Analysis) indicates a good separation of the dry cured ham samples according to their production process and that it is possible to set up, using data mining methods, classification models with a high success rate in cross validation. Secondly, we exploited the higher mass resolution of the new PTR-ToF-MS, as compared with standard quadrupole based versions, for the identification of the exact sum formula of the mass spectrometric peaks providing analytical information on the observed differences. The work indicates that PTR-ToF-MS can be used as a rapid method for the identification of differences among dry cured hams produced following the indications of different PDOs and that it provides information on some of the major volatile compounds and their link with the implemented manufacturing practices such as rearing system, salting and curing process, manufacturing practices that seem to strongly affect the final volatile organic profile and thus the perceived quality of dry cured ham.
The following values have no corresponding Zotero field: accession-num: 21645714
Keywords: Animals; Data Mining; Dry cured ham; Flavour compounds; Food Handling; Food Handling: methods; Italy; Mass spectrometry; Mass Spectrometry: methods; Meat Products; Meat Products: analysis; PDO; PTR-MS; PTR-ToF-MS; Spain; Swine; volatile compounds; Volatile Organic Compounds

Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. - Echevarría-Zomeño, Sira; Ariza, David; Jorge, Inmaculada; Lenz, Christof; Del Campo, Antonio; Jorrín, Jesús V; Navarro, Rafael M (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.
Keywords: Drought stress; Holm oak proteome; Mass spectrometry; Quercus ilex

Changes in the protein profile of Quercus ilex leaves in response to drought stress and recovery. - Echevarría-Zomeño, Sira; Ariza, David; Jorge, Inmaculada; Lenz, Christof; Del Campo, Antonio; Jorrín, Jesús V.; Navarro, Rafael M. (Journal of plant physiology, 2009)
To characterize the molecular response of holm oak to drought stress and its capacity to recover 9-month-old Quercus ilex seedlings were subjected to three treatments for a 14-d period: (i) continuous watering to field capacity (control plants, W), (ii) no irrigation (drought treatment, D), and (iii) no irrigation for 7d followed by a watering period of 7d (recovery treatment, R). In drought plants, leaf water potential decreased from -0.72 (day 0) to -0.99MPa (day 7), and -1.50MPa (day 14). Shoot relative water content decreased from 49.3% (day 0) to 47.7% (day 7) and 40.8% (day 14). Photosystem II quantum yield decreased from 0.80 (day 0) to 0.72 (day 7) and 0.73 (day 14). Plants subjected to water withholding for 7d reached, after a 7-d rewatering period, values similar to those of continuously irrigated control plants. Changes in the leaf protein pattern in response to drought and recovery treatments were analyzed by using a proteomic approach. Twenty-three different spots were observed when comparing the two-dimensional electrophoresis profile of control to both drought and recovered plants. From these, 14 proteins were identified from tryptic peptides tandem mass spectra by using the new Paragon algorithm present in the ProteinPilot software. The proteins identified belong to the photosynthesis, carbohydrate and nitrogen metabolism, and stress-related protein functional categories.
The following values have no corresponding Zotero field: accession-num: 18778874
Keywords: Drought stress; Holm oak proteome; Mass spectrometry; Quercus ilex

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity